PENINGKATAN PEREKONOMIAN PETANI MELALUI PEMBUATAN BENIH PADI KELAS SEBAR (EXTENSION SEED) - Waluyo, Alif; Ahzar, Fahri Ali (Sekolah Tinggi Ilmu Ekonomi AMA, 2024)
The economy of farmers in Indonesia can be said to not be in good condition. Only a small number of farmers have been financially successful. The government's role in improving the welfare of farmers has been carried out by paying great attention to the agricultural sector. Sukoharjo Regency is a major contributor to the regional economy through the agricultural sector. In order for the economy of farmers in Sukoharjo Regency to be optimal, training is provided on making rice seeds in the distribution class. The method used in the community service program is through Asset Based Community Development (ABCD). Training and counseling are carried out for the